Neointimal coverage and late apposition of everolimus-eluting bioresorbable scaffolds implanted in the acute phase of myocardial infarction: OCT data from the PRAGUE-19 study - Toušek, Petr; Kočka, Viktor; Malý, Martin; Lisa, Libor; Buděšínský, Tomáš; Widimský, Petr (Heart and vessels, 2016)
Incomplete stent apposition and uncovered struts are associated with a higher risk of stent thrombosis. No data exist on the process of neointimal coverage and late apposition status of the bioresorbable vascular scaffold (BVS) when implanted in the highly thrombogenic setting of ST-segment elevation acute myocardial infarction (STEMI). The aim of this study was to assess the serial changes in strut apposition and early neointimal coverage of the BVS using optical coherence tomography (OCT) in selected patients enrolled in the PRAGUE-19 study. Intracoronary OCT was performed in 50 patients at the end of primary percutaneous coronary intervention for acute STEMI. Repeated OCT of the implanted BVS was performed in 10 patients. Scaffold area, scaffold mean diameter and incomplete strut apposition (ISA) were compared between baseline and control OCT. Furthermore, strut neointimal coverage was assessed during the control OCT. Mean scaffold area and diameter did not change between the baseline and control OCT (8.59 vs. 9.06 mm(2); p = 0.129 and 3.31 vs. 3.37 mm; p = 0.202, respectively). Differences were observed in ISA between the baseline and control OCT (0.63 vs. 1.47 %; p < 0.05). We observed 83.1 % covered struts in eight patients in whom the control OCT was performed 4-6 weeks after BVS implantation, and 100 % covered struts in two patients 6 months after BVS implantation. Persistent strut apposition and early neointimal coverage were observed after biodegradable vascular scaffold implantation in patients with acute ST-segment elevation myocardial infarction.
Keywords: Coronary Angiography; Neointima; Prospective Studies; infarkt myokardu s elevacemi ST úseků; Humans; Absorbable Implants; lidé středního věku; prospektivní studie; everolimus; Middle Aged; neointima; Percutaneous Coronary Intervention; Czech Republic; optická koherentní tomografie; Time Factors; koronární cévy; mužské pohlaví; Cardiovascular Agents; Česká republika; Everolimus; kardiovaskulární látky; Tomography, Optical Coherence; Prosthesis Design; výsledek terapie; časové faktory; Treatment Outcome; koronární angioplastika; ženské pohlaví; Coated Materials, Biocompatible; lidé; ST Elevation Myocardial Infarction; Coronary Vessels; biokompatibilní potahované materiály; Aged; protézy - design; senioři; vstřebatelné implantáty; Male; koronární angiografie; Female